TINJAUAN TERHADAP PELANGGARAN LALU LINTAS KENDARAAN RODA DUA OLEH ANAK DI BAWAH UMUR DI WILAYAH HUKUM POLRESTA BUKITTINGGI - Saputra, Tomi; Sukmareni; Zulfiko, Riki (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
Two-wheeled vehicle traffic violations committed by minors in the jurisdiction of the City of Bukittinggi still occur a lot and have even increased from year to year. This study aims to find out how law enforcement is against violations of two-wheeled vehicle traffic by minors and the constraints and efforts made to enforce the law on traffic violations of minors. This study uses empirical legal research methods. The results of this study, namely: 1) Law enforcement of traffic violations by minors in the City of Bukittinggi, is by Law Number 22 of 2009 concerning Road Traffic and Transportation, but there are still obstacles in its implementation, 2) Efforts law enforcement of two-wheeled vehicle traffic violations by minors has been carried out to the maximum extent possible by the Bukittinggi Police Traffic Unit, but in making these efforts there are obstacles encountered. These efforts are in the form of pre-emptive (coaching), preventive (counseling), and repressive (action) legal remedies.